2012
DOI: 10.1021/nn301148e
|View full text |Cite
|
Sign up to set email alerts
|

αVβ3 Integrin-Targeted PLGA-PEG Nanoparticles for Enhanced Anti-tumor Efficacy of a Pt(IV) Prodrug

Abstract: Targeted delivery of therapeutics to tumor neovasculature is potentially a powerful approach for selective cancer treatment. Integrins are heterodimeric transmembrane proteins involved in cell adhesion and cell signaling, and their expression is commonly upregulated in cancers and inflammatory diseases. The αvβ3 integrin is differentially upregulated on angiogenic endothelial cells as well as on many cancer cells. Here we demonstrate the differential targeting of cisplatin prodrug-encapsulated poly(D,L-lactic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
225
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(228 citation statements)
references
References 55 publications
3
225
0
Order By: Relevance
“…However, these changes were so minimal that they could be ignored, as they would not have changed the in vitro and in vivo behavior of NPs. 31 Conjugation efficiency of CREKA with nanoparticles and creKa density on the nanoparticle surface Under our experiment conditions (mass ratio of Mal-PEG-PLA to CREKA 3 mg:18 μg, reaction time 4 hours), only about 0.6 μg of free CREKA was detected in the supernatant, and the CREKA conjugation efficiency was approximately 96.7%. The density of CREKA on the surface of NPs was 220±36, which is reasonable for an actively targeting drugdelivery system.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, these changes were so minimal that they could be ignored, as they would not have changed the in vitro and in vivo behavior of NPs. 31 Conjugation efficiency of CREKA with nanoparticles and creKa density on the nanoparticle surface Under our experiment conditions (mass ratio of Mal-PEG-PLA to CREKA 3 mg:18 μg, reaction time 4 hours), only about 0.6 μg of free CREKA was detected in the supernatant, and the CREKA conjugation efficiency was approximately 96.7%. The density of CREKA on the surface of NPs was 220±36, which is reasonable for an actively targeting drugdelivery system.…”
mentioning
confidence: 84%
“…31,32 The in vitro release curves showed that the conjugation of CREKA did not significantly change the release profiles of DiR or coumarin 6 from NPs (Figure 2A, B). After 72 hours, the cumulative release of DiR was lower than 1% in PBS (pH 7.4) and approximately 3% in 10% FBS.…”
Section: In Vitro Release Profilesmentioning
confidence: 97%
“…[9][10][11] The α v β 3 integrin is another receptor that is frequently targeted and exploited to enhance cellular internalization by decorating delivery systems with the arginine-glycine-aspartic acid tripeptide ligand. [12][13][14] A third example of a receptor that is exploited for tumor targeting is the epidermal growth factor receptor (EGFR), which is generally overexpressed and therefore used in the treatment of neck cancer, glioblastoma, and lung adenocarcinoma. [15] To this purpose, antibodies, aptamers, and peptides were designed as targeting ligands.…”
Section: Introductionmentioning
confidence: 99%
“…PLGA, a controlled release polymer, has been used in the preparation of a wide variety of drug delivery systems, because its safety in the clinic is well established. 23,24 PLGA can protect loaded drug from degradation. Sustained release of drug from NPs based on PLGA is …”
Section: Introductionmentioning
confidence: 99%